Perbedaan Pasta Gigi dengan dan Tanpa Tambahan Ekstrak Etanol Daun Belimbing Wuluh (Averrhoa Bilimbi L.) Konsentrasi 10,5% Terhadap Hambatan Pertumbuhan Streptococcus Mutans - Sharastiti, Riesky; , drg. Mahmud Kholifa, MDSc; , drg. Nilasary Rochmanita S, MDSc (2015)
Streptococcus mutans is known as the main bacteria causes dental caries. Dental caries can be avoided by applying toothpaste contains antibacteria and this antibacteria ability can be enhanced by adding herbal materials with 10,5% consentration of ethanol extract of bilimbi leaf (Averrhoa bilimbi L.). The aims of study were to know the difference between toothpaste with and without additional ethanol extract of bilimbi leaf on growth inhibition of Streptococcus mutans and to examine ethanol extract of bilimbi leaf to increase antibacteria ability of toothpaste to inhibit Streptococcus mutans. The true experimental laboratory with postest only control group design was performed in this study. The experimental was devided into three groups included toothpaste with and without ethanol extract of bilimbi leaf and aquabidest used as negative control. Diffusion prosedure was delivered to know the inhibitory zone. The result, toothpaste without ethanol extract of bilimbi leaf had clear zone stronger than toothpaste with ethanol extract of bilimbi leaf and negative control was p=0,000, meanwhile toothpaste with ethanol extract of bilimbi leaf could not increase antibacterial ability of toothpaste to inhibit Streptococcus mutans was p=0,000. In conclusion, toothpaste with and without ethanol extract of bilimbi leaf had potensial to inhibit Streptococcus mutans but ethanol extract of bilimbi leaf could not increase antibacterial ability of toothpaste to inhibit Streptococcus mutans.